Surgery in and around the Orbit CrossRoads - Gooris, Peter J.J; Mourits, Maarten P.; Bergsma, J.Eelco (Springer Nature, 2023)
This OpenAccess - textbook sheds new light on pathology in and around the orbit, which is typically an area where many medical disciplines overlap. Each physician brings a specific expertise, but the goal should be that the end result of all this input is much more than the sum of the parts. Collaboration, insight and overall knowledge of all parties involved are essential to achieve an optimal patient outcome. Oral and Maxillofacial surgeons have traditionally focused on the bony parts of the orbit, but usually have limited knowledge of the intricacies of binocular single vision, and for the Ophthalmologist it may be the other way around. In the past, scientific articles were often written from a single point of view, resulting in tunnel vision for the physician. The multidisciplinary approach to the orbit leads to an improvement in treatment that should not be underestimated and from which the patient benefits immensely. But especially for the physician and the trainees, a multidisciplinary consultation is a real goldmine in which a lot can be gained. Not every medical problem needs to be tackled in a multidisciplinary framework, but problems around the eye socket often do. At Amphia Hospital in Breda, the Netherlands, more than fifteen years ago, a collaboration between Oral and Maxillofacial Surgeons, Endocrinologists, Radiologists and Ophthalmologists was initiated, which has proven to be very fruitful. The main focus was on Graves' Orbitopathy and orbital fractures, but problems associated with these conditions were also frequently encountered. For those who want to follow this example, or for those who are interested in both orbital surgery, anatomy or ophthalmological orbital issues, this book could prove to be complementary.